-3(6x-5)+2x-(11x+8)=

Simple and best practice solution for -3(6x-5)+2x-(11x+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6x-5)+2x-(11x+8)= equation:


Simplifying
-3(6x + -5) + 2x + -1(11x + 8) = 0

Reorder the terms:
-3(-5 + 6x) + 2x + -1(11x + 8) = 0
(-5 * -3 + 6x * -3) + 2x + -1(11x + 8) = 0
(15 + -18x) + 2x + -1(11x + 8) = 0

Reorder the terms:
15 + -18x + 2x + -1(8 + 11x) = 0
15 + -18x + 2x + (8 * -1 + 11x * -1) = 0
15 + -18x + 2x + (-8 + -11x) = 0

Reorder the terms:
15 + -8 + -18x + 2x + -11x = 0

Combine like terms: 15 + -8 = 7
7 + -18x + 2x + -11x = 0

Combine like terms: -18x + 2x = -16x
7 + -16x + -11x = 0

Combine like terms: -16x + -11x = -27x
7 + -27x = 0

Solving
7 + -27x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -27x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -27x = 0 + -7
-27x = 0 + -7

Combine like terms: 0 + -7 = -7
-27x = -7

Divide each side by '-27'.
x = 0.2592592593

Simplifying
x = 0.2592592593

See similar equations:

| 29-8x=0 | | 6(x-4)+10(2x+3)= | | 6/-2 | | 2m-3n=8 | | 10-4(6-x)+5x= | | 24-22=1 | | 8x-(4x-5)=17 | | 33/49*14/45*27/22 | | 3/2w-7/5w=-1/20 | | 4x-10=-6 | | (U+5)(u-3)= | | x-1/2x+14-x+5/9x+63 | | Ln(200)=ln(27x)+0.2x | | m+22=21 | | (2w^3-9w^5+2)10w^4= | | 2x+1=3y | | 8x^4(2-5x^2)= | | 180=12*x | | 6w^3(9w^7+4w)= | | 13=2*3.14*x | | (7/6n)+(1/2n)=5 | | 10.99=2*3.14*x | | 3x+6y=-2 | | 37.7=2*3.14*x | | 9x/2=49.5 | | x^2+x+5=65 | | 14x=49.5 | | (2w^2-7w^4+7)3w^5= | | 7x/2=49.5 | | 9w^2-9=0 | | 6y^2(10-9y^3)= | | 9(2x+5)=6(x-2)-3 |

Equations solver categories